Tourism marketing : a strategic approach - Ray, Nilanjan, 1984-; Das, Dilip Kumar, 1974-; Kumar, Raj, 1959- (Apple Academic Press, 2017)
"Tourism Marketing: A Strategic Approach presents a variety of practical application tools, skills, practices, models, approaches, and strategies that are proving themselves effective in tourism marketing. The volume considifers overall infrastructure, socioeconomic conditions, and modifern tourism business infrastructure in discussing the efficiency of good strategies and practices and their impact on business and economic growth. Tourism is one of the fastest growing industries, and in the next few decades, it will play a role in many fields, such human resources, national economic growth, and more."- Resumé vydavatel